Corporate social responsibility: does inventory management matter?. (2015) - Elsayed, Khaled
Although the importance of both inventory management and social responsibility is well acknowledged in the literature related to supply chain management, studies that investigate the relationship between social responsibility and inventory management are rare. Consequently, this study took a step toward filling this knowledge gap by providing empirical evidence regarding the impact of inventory management on corporate social responsibility. The study also adds to literature by conducting research on a sample of listed firms from Egypt as a developing country, where much of the existing evidence reflects experience from developed countries. Econometric analysis demonstrated that the null hypothesis of no impact of inventory management on corporate social responsibility can be rejected. Rather, the findings provided strong evidence that inventory management positively affects corporate social responsibility. This conclusion was robust to the inclusion of a wide range of control variables and the use of more than one estimation model.